2020
DOI: 10.1097/dss.0000000000002553
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Postsurgical Scars Between Vegan and Omnivore Patients

Abstract: BACKGROUND Postsurgical skin healing can result in different scars types, ranging from a fine line to pathologic scars, in relation to patients' intrinsic and extrinsic factors. Although the role of nutrition in influencing skin healing is known, no previous studies investigated if the vegan diet may affect postsurgical wounds. OBJECTIVE The aim of this study was to compare surgical scars between omnivore and vegan patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Several anecdotal cases had focused on vegetarian diet in humans with discordant results in establishing a potential cause-effect link between furocumarin-rich foods intake and a potential photosensitivity modification, conversely we found that a higher dietary intake of furocumarins in vegan and vegetarian diets is associated with greater skin sensitivity to NB-UVB phototherapy in psoriatic patients. Due to the increased prevalence of vegans and vegetarians among psoriatic patients [ 35 ], dermatologists started to evaluate potential differences in clinical outcomes and therapeutic management [ 36 , 37 ]. Although the Mediterranean diet, which is rich in vegetables, is regarded as beneficial for psoriatic patients [ 1 ], the impact of the single-food ingredients on phototherapy is entirely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several anecdotal cases had focused on vegetarian diet in humans with discordant results in establishing a potential cause-effect link between furocumarin-rich foods intake and a potential photosensitivity modification, conversely we found that a higher dietary intake of furocumarins in vegan and vegetarian diets is associated with greater skin sensitivity to NB-UVB phototherapy in psoriatic patients. Due to the increased prevalence of vegans and vegetarians among psoriatic patients [ 35 ], dermatologists started to evaluate potential differences in clinical outcomes and therapeutic management [ 36 , 37 ]. Although the Mediterranean diet, which is rich in vegetables, is regarded as beneficial for psoriatic patients [ 1 ], the impact of the single-food ingredients on phototherapy is entirely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…To further empower this statement, small amounts of dietary intake of furocumarins were reported to trigger photoxicity in both PUVA and NB-UVB [ 20 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that wound diastasis was more prevalent among vegans, and after a 6-month period, vegan patients had higher modified SCAR scores compared to omnivores, indicating more pronounced scar spread, a higher incidence of atrophic scars, and a poorer overall impression. Finally, they concluded that a vegan diet may have a detrimental impact on the outcome of surgical scars [ 44 ] Table 1 .…”
Section: Plant-based Diet Effects On Other Skin Conditionsmentioning
confidence: 99%
“…On the contrary, proper preoperative feeding stimulates the healing process, since certain nutrients (such as glutamine, arginine, butyrate, and antioxidants) play an important role in regulating broblast proliferation and regulating type I and III collagen deposition [18]. A vegan diet has been reported to exert a negative impact on the outcome of surgical scars [19]. Therefore, evaluating the preoperative nutritional status of patients is crucial for the early rise and prevention of HS formation.…”
Section: Introductionmentioning
confidence: 99%